1987
DOI: 10.1016/s0022-5347(17)43864-x
|View full text |Cite
|
Sign up to set email alerts
|

Stage T1, Grade 3 Transitional Cell Carcinoma of the Bladder: An Unfavorable Tumor?

Abstract: Transurethral resection only was performed in 172 patients with initial stage Ta, T1 transitional cell carcinoma of the bladder. Additional treatment during the course of disease was given to 9 patients with carcinoma in situ and to 8 patients with tumor progression. The mean followup was 106 months. The 10-year survival rates were 95 per cent for patients with stage Ta, grade 1 disease, 89 per cent for stage Ta, grade 2, 84 per cent for stage Ta, grade 3, 78 per cent for stage T1, grade 2 and 50 per cent for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
1
3

Year Published

1990
1990
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(82 citation statements)
references
References 23 publications
9
69
1
3
Order By: Relevance
“…High-grade Ta tumours account for only 2% to 9% of all cases of NMIBC. 16,17 Holmang and colleagues demonstrated that low-grade Ta tumours had a recurrence of 70%, with a progression of only 2%. 18 Heney and colleagues showed that the risk of progression to muscle invasion is strongly associated with tumour grade.…”
Section: Stage and Gradementioning
confidence: 99%
“…High-grade Ta tumours account for only 2% to 9% of all cases of NMIBC. 16,17 Holmang and colleagues demonstrated that low-grade Ta tumours had a recurrence of 70%, with a progression of only 2%. 18 Heney and colleagues showed that the risk of progression to muscle invasion is strongly associated with tumour grade.…”
Section: Stage and Gradementioning
confidence: 99%
“…In fact, tumour grade may influence recurrence and progression [3]. T1 G3 tumours in particular are known to have a poor prognosis (from 50 to 70% of recurrence) [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Two major options are available for the management of patients with T1HG tumors: TURBT followed by intravesical therapy, or immediate radical cystectomy. Immediate cystectomy may give the advantage of long term cancer cure; however, it is considered an over-treatment in several cases [15] and carries serious impairment on patient's quality of life, in addition to high morbidity and mortality rates, not less than cystectomy done for invasive disease [16]. Considering survival, Kulkarni et al estimated that a healthy 60 years-old patient undergoing cystectomy for high risk non-muscle invasive disease has a life expectancy of 14.29 yrs compared to 13.63 yrs in similar patient undergoing conservative management [17].…”
Section: Discussionmentioning
confidence: 99%